2021
DOI: 10.1080/23766808.2020.1869900
|View full text |Cite
|
Sign up to set email alerts
|

Responses ofPolylepisbirds to patch and landscape attributes in the High Andes

Abstract: Habitat loss and fragmentation can devastate biodiversity, especially at regional and global scales. However, generalizing to individual species is challenging given the wide variety of intrinsic and extrinsic factors that shape species-specific responses -particularly among species that are specialists, generalists, or adapted to naturally patchy landscapes. In this study, we examined how patch and landscape attributes affected bird communities within Polylepis forest ecosystems, which are patchily distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
(171 reference statements)
0
2
0
2
Order By: Relevance
“…Therefore, in the restoration site, the presence of species categorized as of conservation priority, such as Cinclodes olrogi [22], reinforces the importance of projects like the present one to promote the recovery of specialist birds of this particular ecosystem [45][46][47], whose bird richness depends on patch connectivity and conservation [9]. In turn, a recent study found no evidence that Polylepis specialist bird species were sensitive to patch size, and indicated the high ecological value of small patches for their conservation [48].…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, in the restoration site, the presence of species categorized as of conservation priority, such as Cinclodes olrogi [22], reinforces the importance of projects like the present one to promote the recovery of specialist birds of this particular ecosystem [45][46][47], whose bird richness depends on patch connectivity and conservation [9]. In turn, a recent study found no evidence that Polylepis specialist bird species were sensitive to patch size, and indicated the high ecological value of small patches for their conservation [48].…”
Section: Discussionmentioning
confidence: 63%
“…in Paria Valley, most trees of P. albicans are 4–7 m tall (maximum 10–12.5 m) with diameters of 10–20 cm (maximum 50–60 cm) ( Castro and Flores 2015 ). The Polylepis forests in this region harbor diverse bird communities with a substantial proportion of threatened species, some of which are specialized to Polylepis forests ( Sevillano-Ríos et al 2011 ; Sevillano-Ríos and Rodewald 2017 , 2021 ).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Las plantaciones con especies exóticas de Polylepis debería ser evitada debido a que estas podrían hibridarse con las especies nativas y afectar negativamente la diversidad genética local [29]. La conservación de los bosques pequeños es tan importante como el de los grandes [65,66], ya que, en conjunto, los pequeños representan una gran proporción de la cantidad de total de bosques de ambas especies y podrían ser el hábitat clave para algunas especies de importancia para la conservación [41,66]. Finalmente, creemos que nuestra aproximación para determinar el nicho y la cobertura de estas dos especies puede aplicarse a muchas otras.…”
Section: Implicancias Para La Conservación Y Futuros Estudiosunclassified